Efficacy of Hybrid Endoscopic Submucosal Dissection to Ensure Adequate Submucosal Layer for T1b Colorectal Carcinomas of 20-30 mm in Diameter - Yudai Takehara; Ken Yamashita; Shin Morimoto; Fumiaki Tanino; Noriko Yamamoto; Yuki Kamigaichi; Hidenori Tanaka; Hidehiko Takigawa; Yuji Urabe; Toshio Kuwai; Koji Arihiro; Shiro Oka (Journal of the Anus, Rectum and Colon)
Objectives: Although hybrid endoscopic submucosal dissection (ESD) has gained popularity over the years, its usefulness in ensuring an adequate submucosal [SM] layer for T1b (SM invasion depth 1,000 μm) colorectal carcinoma (CRC) remains unknown. We retrospectively compared conventional ESD (C-ESD) with planned hybrid ESD (PH-ESD) for cT1b CRCs measuring 20-30 mm. Methods: We analyzed 71 consecutive cases of cT1b CRC (20-30 mm). The patients were classified into C-ESD (n=38), PH-ESD (n=21), or salvage hybrid ESD (n=12) groups. We compared the clinicopathological characteristics, including resected SM and vertical margin (VM) distance, and outcomes between the C-ESD and PH-ESD groups. We also investigated the factors leading to VM positivity (VM1). Results: The PH-ESD group exhibited a significantly shorter procedure time (40.5 vs. 60.5 min) and a significantly higher rate of VM 500 μm (81.0% vs. 47.4%) compared to the C-ESD group. Regarding superficial tumors, the PH-ESD group exhibited significantly longer resected SM (1,243 vs. 837 μm) and VM (545 vs. 302 μm) distances and a significantly higher rate of VM 500 μm (72.7% vs. 14.3%) than the C-ESD group. All VM1 lesions were resected using C-ESD or salvage hybrid ESD. VM1 lesions exhibited significantly higher rates of poorly differentiated histology at the deepest invasive front (71.9% vs. 14.3%) and perioperative perforation (28.6% vs. 0%) than VM-negative lesions. Conclusions: PH-ESD for 20-30-mm T1b CRCs may be more useful than C-ESD in terms of procedure time, especially for superficial lesions, ensuring a longer resected SM distance and VM 500 μm.